Efficiently Estimating Soil Moisture Content: Adopting IoT Technologies - Mohanbabu, M.; Vasista , T. G.; Giridhar, T.; Koteswararao, K. (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
Soil moisture plays a major role in agricultural yield, hydrological, and environmental monitoring studies. Soil-moisture’s accurate estimation is important for successfully improving crop yield efficiently using agricultural resources and effectively managing water resources. The current article aims to list different approaches to estimating soil moisture such as using microwave, radar, and sensor-based methods of electronic and communication engineering and also IoT-based methods from computer engineering fields to find the journey of use of state-of-the-art technology methods for measuring soil moisture. Out of the mentioned methods, Sensor & IoT-based method is playing a vital role and is currently being used in advanced countries. Therefore this research is focused on experimenting the water flow control and measurement of soil moisture using sensors on micro-controller-based prototypes. Experiments showed that it is feasible to estimate the requirement of water more accurately than traditional methods. Thus more water savings can be benefited.